Os trabalhadores do Café: análise de uma obra de Portinari - Bernardo, Hebe Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The main objective of this research is the analysis of the work Café of 1935 by Cândido Portinari, as well as their preparatory studies. During the construction of this research project realized the need to insert the derivations of the work dating from 1934 – 1938 of Café, these works introduced in preparatory drawings, panels and frescoes, each within the context of social history in the painter Portinari in the 30’s. These parties have completed the importance of the whole and vice versa, in view of the dialectical relations of the subject and object which resulted in the creation of the artistic object through the social context that influenced the development of the artist.Contributed to the preparation of the content of this survey the history of blacks and immigrants in the coffee culture in the direct relationship of these characters with the work, because it is through them that Portinari demonstrated a social concern.Another important aspect is the iconography and sociological aspects of art Portinari pointing to the field of understanding the meaning work, the national and universal historical events that permeated Café and modernism in and outside of Brazil and its social repercussions.In the field of Gestalt theory, the search will be contemplated with the interpretation noting the contents of Café shape while reading ability

O objetivo principal dessa pesquisa é a análise da obra Café de 1935 de Cândido Portinari, bem como seus estudos preparatórios. Durante a construção deste projeto de pesquisa percebi a necessidade de inserir as derivações da obra que datam de 1934 – 1938 de Café, obras estas introduzidas em desenhos preparatórios, painéis e afrescos, cada uma dentro do contexto histórico social do pintor Portinari marcados na década de trinta. Essas partes completaram a importância do todo e vice-versa, tendo em vista as relações dialéticas do sujeito e objeto que implicaram na criação do objeto artístico por meio do contexto social que influenciaram a elaboração do artista. Contribuíram para a elaboração do conteúdo desta pesquisa a história dos negros e imigrantes na cultura do café, na relação direta destes personagens com a obra, pois são por meio deles que Portinari demonstrou uma preocupação social. Outro aspecto relevante é a iconografia e aspectos sociológicos da arte Portinari que apontam para o campo do entendimento do significado da obra, os acontecimentos históricos universais e nacionais que permearam Café e o modernismo dentro e fora do Brasil e suas repercussões sociais. No campo da teoria da Gestalt, a pesquisa será contemplada com a interpretação de Café ressaltando os conteúdos da forma enquanto possibilidade de leitura
Keywords: Portinari, Cândido, 1903-1962; Arte brasileira; Arte; Arte - Brasil; Gestalt; Visual arts; Gestalt; Iconography - Brazil